Features and methods of heavy sour crude oil refining - Гринишин, Олег Богданович; Мохаммад, Шакир Абд Ал-Амери; Хлибишин, Юрий Ярославович (Eastern-European Journal of Enterprise Technologies, 2013)
The features and properties of distillate fractions and residue of heavy sour crude Orkhovitsk oil were examined and promising methods for their use were proposed in the paper. It was found that with increasing the temperature of fractions boiling, the content of sulfur compounds in them increases. The main regularities of the process of viscosity breaking of Orkhovitsk oil residue in the temperature range 410-450°С were studied. It was established that the process of viscosity breaking can not be considered as an independent and final stage of refining of Orkhovitsk oil residue. It was shown that the method of co-oxidation of Orkhovitsk oil residue and 11-13% masses of heavy pyrolysis resin at the temperature of 250°С, air supply 2.5h-1 during 6 hours allows obtaining the bitumen, which, by the main quality parameters, meets the requirements for road bitumen of the grade BND 60/90 according to DSTU 4044-2001. As a result of studying the basic regularities of modification of residual bitumen obtained from Orkhovitsk oil by the polymer latex Butonal NS 198, it was determined that inclusion of 2-3% masses of this modifier into bitumen, followed by mixing at 180°C for 2-6 h, allows obtaining the bitumen, which meets the requirements of the grade BND 60/90.